The Zebrafish Amygdaloid Complex – Functional Ground Plan, Molecular Delineation, and Everted Topology - Porter, Baylee A.; Mueller, Thomas (Frontiers in Neuroscience, 2020)
In mammals and other tetrapods, a multinuclear forebrain structure, called the amygdala, forms the neuroregulatory core essential for emotion, cognition, and social behavior. Currently, higher circuits of affective behavior in anamniote non-tetrapod vertebrates (“fishes”) are poorly understood, preventing a comprehensive understanding of amygdala evolution. Through molecular characterization and evolutionary-developmental considerations, we deduced the complex amygdala ground plan of zebrafish, whose everted telencephalon has made comparisons to the evaginated forebrains of tetrapods challenging. In this radical paradigm, thirteen telencephalic territories constitute the zebrafish amygdaloid complex and each territory is distinguished by conserved molecular properties and structure-functional relationships with other amygdaloid structures. Central to our paradigm, the study identifies the teleostean amygdaloid nucleus of the lateral olfactory tract (nLOT), an olfactory integrative structure that links dopaminergic telencephalic groups to the amygdala alongside redefining the putative zebrafish olfactory pallium (“Dp”). Molecular characteristics such as the distribution of substance P and the calcium-binding proteins parvalbumin (PV) and calretinin (CR) indicate, that the zebrafish extended centromedial (autonomic and reproductive) amygdala is predominantly located in the GABAergic and isl1-negative territory. Like in tetrapods, medial amygdaloid (MeA) nuclei are defined by the presence of substance P immunoreactive fibers and calretinin-positive neurons, whereas central amygdaloid (CeA) nuclei lack these characteristics. A detailed comparison of lhx5-driven and vGLut2a-driven GFP in transgenic reporter lines revealed ancestral topological relationships between the thalamic eminence (EmT), the medial amygdala (MeA), the nLOT, and the integrative olfactory pallium. Thus, the study explains how the zebrafish amygdala and the complexly everted telencephalon topologically relate to the corresponding structures in mammals indicating that an elaborate amygdala ground plan evolved early in vertebrates, in a common ancestor of teleosts and tetrapods.